The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1532-5415.1993.tb07298.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Depressive Symptoms in Younger and Older Medical Inpatients with Major Depression

Abstract: Cognitive symptoms of depression can help to distinguish medical inpatients with and without MDD. In older adults, however, somatic symptoms cannot be ignored and may be more important for diagnosing MDD than previously realized. These findings will help clinicians identify patients with MDD and differentiate them from non-depressed patients with medical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 47 publications
1
59
1
Order By: Relevance
“…For example, our estimates of the frequency of comorbid psychiatric conditions generated from prior outpatient visits are consistent with previous reports that relied on interviews of patients to identify comorbid psychiatric conditions. 7,[13][14][15][16] For example, Koenig et al 13 reported rates of depressive disorders as high as 45% among geriatric patients admitted to critical care settings. Similar results were reported in 2 other studies 14,15 in which researchers estimated the prevalence of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our estimates of the frequency of comorbid psychiatric conditions generated from prior outpatient visits are consistent with previous reports that relied on interviews of patients to identify comorbid psychiatric conditions. 7,[13][14][15][16] For example, Koenig et al 13 reported rates of depressive disorders as high as 45% among geriatric patients admitted to critical care settings. Similar results were reported in 2 other studies 14,15 in which researchers estimated the prevalence of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in several studies [13][14][15][16] have examined the potential adverse effects of the intensive care unit (ICU) on the development of psychiatric disorders, whereas few have examined the effects of existing psychiatric disorders on the outcomes of patients admitted to ICUs. Most of this work has been focused on patients who have had an AMI.…”
mentioning
confidence: 99%
“…Its prevalence is 1-5% among ambulatory patients, 13% among institutionalised patients [71] and 40% in patients with respiratory failure. YOANNES et al [72] showed that the rate of depression in a group of 96 elderly COPD patients was significantly higher than in healthy or otherwise disabled elderly subjects.…”
Section: Anxiety and Depression Disordersmentioning
confidence: 99%
“…The authors of one of the reviews [7] and others [3,[10][11][12] have argued that existing studies linking depression to cardiac and all-cause mortality post-AMI have not adequately controlled for confounding in measurement of depressive symptoms related to overlap between somatic symptoms ofdepression and cardiac symptoms. Indeed, symptoms characteristically associated with depression, such as fatigue, anhedonia, changes in sleep patterns, changes in appetite, or poor concentration, for instance, could occur as a normal reaction to the AMI, from side effects of its treatment, or from the hospitalization itself [13,14]. The BD!…”
Section: Introductionmentioning
confidence: 99%